1996
DOI: 10.1007/bf00333934
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of photosynthetic acclimation and photoinhibition in two evergreen herbs from a winter deciduous forest

Abstract: The relationship between the microclimate within an Oak-Hickory forest and photosynthetic characters of two resident evergreen herbs with contrasting leaf phenologies was investigated on a monthly basis for 1 full year. Heuchera americana has leaf flushes in the spring and fall, with average leaf life spans of 6-7 months. Hexastylis arifolia produces a single cohort of leaves each spring with a leaf life span of 12-13 months. We predicted that among evergreen plants inhabiting a seasonal habitat, a species for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 24 publications
3
33
0
1
Order By: Relevance
“…In general, chlorophyll content decreases with increased irradiance, because when there is greater availability of photosynthetic active radiation, photosystems can operate at satisfactory levels for metabolism with less chlorophyll. On the other hand, low irradiance causes chlorophyll content and accessory pigments to increase so as to absorb more light energy and transfer it to reaction centers (Taiz and Zeiger 2013, Zhang et al 2009). Skillman et al (1996 observed that leaf chlorophyll content was considerably higher in summer for herbaceous species of deciduous forests.…”
Section: Discussionmentioning
confidence: 99%
“…In general, chlorophyll content decreases with increased irradiance, because when there is greater availability of photosynthetic active radiation, photosystems can operate at satisfactory levels for metabolism with less chlorophyll. On the other hand, low irradiance causes chlorophyll content and accessory pigments to increase so as to absorb more light energy and transfer it to reaction centers (Taiz and Zeiger 2013, Zhang et al 2009). Skillman et al (1996 observed that leaf chlorophyll content was considerably higher in summer for herbaceous species of deciduous forests.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, daily average air and leaf temperatures change across the season, and this may also bring about alterations in the shape of J max versus T response curve. Seasonal variability in the temperature optima of net assimilation and J max has been demonstrated in a number of investigations (Mooney et al 1978;Mooney 1980;Skillman, Strain & Osmond 1996) and further studies are necessary to identify the kinetic constants of temperature acclimation.…”
Section: Modifications In Temperature Response Of Photosynthetic Elecmentioning
confidence: 99%
“…Blessed with a diversity of opportunities for support, and augmented by the North Carolina Biotechnology Center gift of the mass spectrometer that attracted a decade of funding from the DOE, research at Duke was just as exciting and as productive of papers as RSBS. To some extent, the weight shifted from postdocs to students; 25% of all students I have cosupervised obtained Duke PhDs from projects that commenced during our three and a half years in Durham (10,55,57,154,182). The failure of three attempts to win funding from multidisciplinary tri-agency programs to support the phytotron research was most disappointing.…”
Section: Department Of Botany Duke University: 1987-1991mentioning
confidence: 99%